2008
DOI: 10.1097/01.prs.0000299379.64906.2e
|View full text |Cite
|
Sign up to set email alerts
|

A Cephalometric Analysis of Maxillary and Mandibular Parameters in Treacher Collins Syndrome

Abstract: This study quantifies the cephalometric dysmorphology of patients with Treacher Collins syndrome and compares it to that of age-matched controls. These cephalometric characteristics have clinical significance in Treacher Collins syndrome and in the planning of bimaxillary advancement and genioplasty in syndrome patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 16 publications
3
29
0
3
Order By: Relevance
“…Other authors have also suffered from groups of patients not truly representative of the TreacherCollins syndrome population and low sample sizes because of the rarity of the condition. 1,17,21 We have shown that geometric morphometrics still has a role in the severely affected child with absent zygomatic arches or complete absence of the orbitozygomatic region. If there is unilateral absence of the orbitozygomatic region secondary to trauma or malignancy, surgeons have used the contralateral normal facial skeleton to design a size-matched zygoma or absent temporomandibular joint process.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other authors have also suffered from groups of patients not truly representative of the TreacherCollins syndrome population and low sample sizes because of the rarity of the condition. 1,17,21 We have shown that geometric morphometrics still has a role in the severely affected child with absent zygomatic arches or complete absence of the orbitozygomatic region. If there is unilateral absence of the orbitozygomatic region secondary to trauma or malignancy, surgeons have used the contralateral normal facial skeleton to design a size-matched zygoma or absent temporomandibular joint process.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have described Treacher-Collins syndrome skull morphology either with cephalography, qualitative analysis using three-dimensional computed tomographic head scans, or volume analysis. 1,[15][16][17][18][19][20] They all use traditional morphometric techniques, which measure lengths, angles, and volumes and relate them to specific defects. However, none of these tools can provide a global picture of the Treacher-Collins syndrome deformity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most severe forms of TCS may have significantly deficient proximal mandible or even lacking the ramus/condyle unit altogether. 33,34,[39][40][41] Hypoplasia of the facial bones may result in dental malocclusion. The teeth may be widely spaced, malpositioned or reduced in number.…”
mentioning
confidence: 99%
“…Na presente casuística, a altura facial total mostrou-se reduzida e a altura ântero-inferior, aumentada, o que difere do observado na STC. Chong et al (2008), comparando dados cefalométricos de 24 adolescentes com STC com dados obtidos do grupo controle (pareado pelo gênero), observaram que a dimensão da maxila na STC é reduzida e a mandíbula é pequena e significativamente rodada para baixo e para trás. De acordo com os autores, a alteração mandibular é responsável pelo perfil facial convexo observado na STC.…”
Section: Dpunclassified